If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -3e = 2 + -5(e + 1) Reorder the terms: 19 + -3e = 2 + -5(1 + e) 19 + -3e = 2 + (1 * -5 + e * -5) 19 + -3e = 2 + (-5 + -5e) Combine like terms: 2 + -5 = -3 19 + -3e = -3 + -5e Solving 19 + -3e = -3 + -5e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '5e' to each side of the equation. 19 + -3e + 5e = -3 + -5e + 5e Combine like terms: -3e + 5e = 2e 19 + 2e = -3 + -5e + 5e Combine like terms: -5e + 5e = 0 19 + 2e = -3 + 0 19 + 2e = -3 Add '-19' to each side of the equation. 19 + -19 + 2e = -3 + -19 Combine like terms: 19 + -19 = 0 0 + 2e = -3 + -19 2e = -3 + -19 Combine like terms: -3 + -19 = -22 2e = -22 Divide each side by '2'. e = -11 Simplifying e = -11
| (y^2+2)(4y+7)= | | 2r^2+3r-20=0 | | (3y-3)(y+3)= | | 5x-3=2+6x | | 7=2r+5r | | -129=-3(8-7p) | | (y+9)(y+6)= | | 5x+1=14x-73 | | 6d-2(d-2)=3(d-12) | | (x+7)(2x^2-6x-2)= | | 5b-3=7b+11 | | 4x+10y=35 | | x(5-x)+4(x^1)= | | (5x-6)(4x-7)= | | (5x-7)(3x-2)= | | -7=12-k | | 4d-3=21 | | -32=x-17 | | 237x^2-56x= | | 8x^5y(9x^2+x^2y^3-8y^4)= | | 5a+13=7e-21 | | 3x^2-19x=63 | | 7y-5y=6 | | (4x-5)+(3x-1)= | | (4x^6)(-2x^5)(3x^9)= | | 24.2-18.5P=6.6P-1.9(9P+2) | | 12=k-2+6k | | (-x^2+3x)+(2x^2+7)+(5x-2)= | | 806-?=368 | | z-4=5 | | q+2=3 | | 5x-8x-7= |